Inmunocastración : alternativa humanitaria y efectiva a la castración quirúrgica de cerdos reproductores de descarte (2011)
ABSTRACT: Immunocastration (IC) of pigs during their finishing phase avoids the traumatic castration surgery (Q) still practiced in many countries to prevent boar taint in pork. We have not found reports on IC evaluated on culled adult boars. In this study we evaluated boar taint, spermatogenesis, and weight loss of adult boars after castration by IC versus Q. A total of 21 boars were used (age: 29 months). The IC boars (n: 12) were injected with Innosure® (Pfizer Inc), with repetition four weeks later. The Q boars (n: 9) were castrated when the IC boars were first injected. Both groups were weighted one month later and slaughtered five weeks after the second injection. Testes of IC slaughtered boars were sampled and compared with the Q group. Odor panels were conducted to test all carcasses and pork. The Q boars lost 0.172 kg BW/animal/ day (p = 0.016), while IC boars did not lose weight (p = 0.359). None of the boars (IC or Q) resulted in tainted pork. The IC testes had lower spermatogenesis compared to Q. It is concluded that IC effectively prevented boar taint through testicle atrophy, and it also resulted in no weight loss after castration. The IC thus becomes an effective and humane castration alternative for these animals.